The Magar Culture and its Changing Trends - Ghartimagar, Manoj (Voice of History, 2025)
The Magar culture, deeply embedded in the traditions, languages, and practices of the Magar people, primarily inhabiting the hilly regions of Nepal, has undergone significant transformations in recent decades. This research paper explores the changes in the Magar culture through the lenses of social, economic, and cultural shifts. With rapid modernisation, globalisation, and urbanisation, traditional Magar practices, rituals, and identity are undergoing substantial changes. This paper highlights the evolving nature of Magar customs, the impact of external influences, and the preservation of traditional practices amidst modernising forces. By examining cultural practices such as language, festivals, religious practices, and social structures, this study offers an in-depth understanding of how Magar culture is adapting to contemporary pressures while also retaining core traditional elements. The paper is presented inductively, and the choice of methodology is qualitative.